Pengaruh Politik Identitas dalam Sosial Media di Tengah Pelaksanaan Pemilu - Maeda, Ni Luh Fransisca Putri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The use of identity politics is still often found in the realm of social media, which will negatively affect the social conditions of society, especially the millennial generation. So that the election process in 2024 will not take place democratically. Identity politics is a manifestation of the wrong political marketing activity. Problems that are often present in the middle of elections are violence/discrimination against the background of social disintegration due to identity politics. The purpose of this study is that the consequences of exploiting identity politics through social media, such as religious sentiments, primordialism, fanaticism, superior attitudes, and others can be prevented/anticipated. The method used in this study is descriptive empirical analysis with a knowledge approach. The technique of collecting data in writing this paper is the literature review method. Qualitative data analysis techniques.